Toxicity assessment of peptaibols and contaminated sediments on Crassostrea gigas embryos - Poirier, Laurence; Quiniou, Francoise; Ruiz, Nicolas; Montagu, Monique; Amiard, Jean-claude; Pouchus, Yves François (Aquatic Toxicology, 2007)
Peptaibols are known membrane-modifying peptides that were recently detected in marine sediments and mussels collected from a shellfish farming area (Fier d'Ars, Atlantic coast, France). In this investigation, embryotoxicity bioassays with oysters (Crassostrea gigas) were performed to assess acute toxicity of alamethicin and different groups of peptaibols produced by a Trichoderma longibrachiatum strain isolated from marine environment. C gigas embryos appeared very sensitive to all the metabolites examined with higher toxic effects for long-sequence peptides (EC50 ranging from 10 to 64nM). D-shaped larvae with mantle abnormality were particularly noticed when peptaibol concentrations increased. Disturbances of embryogenesis were also observed following exposure to organic and aqueous extract of sediments from Fier d'Ars (EC50 = 42.4 and 6.6 g L-1 dry weight, respectively). Although peptaibol concentrations measured in these sediments could explain only a part of the toxic effects observed, this study suggests that these mycotoxins can induce larval abnormalities in a population of exposed animals at environmentally realistic concentrations. Their detection in coastal areas devoted to bivalve culture should be taken into account. (c) 2007 Elsevier B.V. All rights reserved.